GRASSROOTS CAMPAIGN BEFORE AND AFTER “ANTI-SMOKING IN PUBLIC PLACES” POLICY - Arie Rui Hamzah (Program Studi Ilmu Komunikasi Universitas Paramadina, 2022)
After reformation in Indonesia, there is a lot of changing in government policy. Maybe is not fast and comprehensive, the changing is slowly but sure. The policy change start from the biggest problem in Indonesia, which is democracy style to the small things such as seat belt policy. The changing is to sustain of nationality life and of course to fix the entire problem from Soeharto legacy. Many grassroots organizations after the reformation started to campaign for any issues that spread in country. They were showing the idea about responsibility as citizen by watching the government (politic, democracy issues and corruption), environment and social-culture life. The campaign and approached from any organization are different, some doing by using media or make events and some doing by strike or demonstration. What they did is tries to push the government or companies to make an action to change or make new policy that related for better future. After couple month arguing about a new policy, which is prohibition smoking in public places, finally the government is releasing and legalize the policy to public, an auxiliary regulation to the 2005 bylaw on air pollution control, is expected to end any arguments about people's right to breathe clean air. The government start makes cooperation with some ministry department, companies, and grass roots organizations. The purpose is to make success the campaign, by communicate the policy to the public. Keyword: grassroost campaign, anti-smoking, government policy